MASS SPECTROSCOPIC STUDIES OF GLUCOSE AFTER NEUTRON IRRADIATION - Bandurin, Yu.A.; Zavilopulo A.М. Zavilopulo; Remeta, E.Yu.; Vizenko, M.P. (Reports of the National Academy of Sciences of Ukraine, 2023)
The processes of glucose molecule fragmentation after neutron irradiation of its powdered sample using the M-30 microtron were investigated through mass spectrometry. For the first time, significant changes in the yield of fragment ions following irradiation were observed. It is shown that neutron interaction results in the breaking of crucial carbon bonds, leading to an increased intensity output of several fragments, particularly significant for m/z = 18, 31, 43, when compared to non-irradiated ones.